Implementation of Computational Thinking in Data Structure Subject Using Problem-based Learning Models - Rafli, Muhammad; Sutarno, Heri; Wihardi, Yaya (Universitas Pendidikan Indonesia, 2023)
Computational thinking skills are one of the skills required in the 21st century. Computational thinking can teach students to think logically, critically, and use appropriate and efficient strategies in solving problems. However, computational thinking skills require an appropriate learning approach. Learning process must be designed to hone problem-solving skills and to acquire essential knowledge and concepts of the subject matter. This study aims to develop a computational approach media with thinking and problem-based learning and to improve students cognitive. This study uses a Comprehensive Life Cycle (SHM) methodology to develop the media. One-group pretest-postest was used for the research design. Media with computational thinking and problem-based learning approach have been developed and has obtained a score of 90% or